A rapid and convenient method for synthesis of anilinoquinazoline: an improved synthesis of erlotinib derivatives - Zahra Haghighijoo; Zahra Rezaei; Samaneh Taheri; Meysam Jani; Soghra Khabnadideh (Shiraz University of Medical Sciences, 2015)
4-Anilinoquinazolines have been widely studied as anticancer agents. Despite the widespread utility of this class of compounds, the reported syntheses of 4-anilinoquinazolines require multistep and low-yielding pathways. A novel strategy to prepare 4-anilinoquinazoline derivatives based on the cyclization of anthranilic acid is described. By using of dichloro anthranilic acid we could etherified the quinazoline ring in order to mimic the erlotinib structure as a tyrosine kinase inhibitor. Our new compounds contain different substitutions at the meta-positions of the quinazoline ring instead of the ortho-positions of erlotinib. We synthesized ten new 4-anilinoquinazoline derivatives (17-26) in only 4 steps with desirable yields. Key words: Synthesis, Erlotinib, Anilinoquinazolines, EGFR.